The Association between Cardiovascular Risk and Elevated Triglycerides - Djanggan Sargowo; Olivia Handayani (The Indonesian Biomedical Journal, 2017)
BACKGROUND: The association between elevated triglycerides and cardiovascular risk has been extensively studied. The elevated level of triglycerides occurs through abnormalities in hepatic very low-density lipoprotein (VLDL) production and intestinal chylomicron synthesis, dysfunctional lipoprotein lipase (LPL)-mediated lipolysis or impaired remnant clearance.CONTENT: Hypertriglyceridemia (HTG) commonly leads to a reduction in high-density lipoprotein (HDL) and increase in atherogenic small dense low-density lipoprotein (LDL) cholesterol, called the atherogenic dyslipidemia (AD). Triglycerides may also stimulate atherogenesis by mechanisms, such excessive release of free fatty acids, and production of pro-inflammatory cytokines, fibrinogen, coagulation factors and impairment of fibrinolysis. Genetic studies strongly support hypertriglyceridemia (HTG) and high concentration of triglyceride-rich lipoprotein (TRL) as causal risk factors for cardiovascular disease. Therefore, lipid management is crucial in reducing cardiovascular risk. Combination of lipid lowering drug therapy may be needed to achieve both LDL and non-HDL cholesterols treatment goal for cardiovascular disease prevention in patients with elevated triglyceride levels, particularly those with triglyceride ≥500 mg/dL.SUMMARY: LDL and non-HDL cholesterol can be a promising target therapy in HTG. Additional clinical outcomes data are needed to provide a more evidence-based rationale for clinical lipid management of hypertriglyceridemic patients.KEYWORDS: hypertriglyceridemia, non-HDL cholesterol, dyslipidemia, CV risk